Prevalence and impact of allergic rhinitis in school going children - Gupta, Sucheta; Gupta, Vinod; Gupta, Akhil (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Allergic rhinitis (AR) is a chronic inflammatory disorder affecting the nasal mucosa. There is negative impact of AR on several aspects of day to day living and quality of life (QoL), which include: daily functioning, sleep, absenteeism, school productivity and academic performance. Almost 40% of children are being affected by AR. Method: An observational study was conducted on randomly selected 100 parents of school going children aging 2 to 15 years, attending OPD in community health center, Chenani, district Udhampur, J and K, for a period of one year from June 2018 to Nov 2018. Children having frequent episodes of allergic rhinitis were enquired about their history of sneezing, runner itchy nose and eyes, thick mucus, nasal blockage or breathless with associated symptoms were selected. Results: 81% of subjects had a worse problem during specific months of the year; and 67% had itchy-watery eyes. In 15% of subjects, AR impacted daily activities. A prevalence of 28% for nasal symptoms and 14% for allergic rhino-conjunctivitis was found. Study also showed significantly higher proportion of blockers (61%) than sneeze runners (39%). 56% children had one or more co morbidity, whereas 44% had ‘nil’ co-morbidities. The most common allergens were: pollens (grass, trees and weeds), house dust mites, pets, molds, fungi and food. Conclusions: AR adversely affects quality of life of patients and furthermore studies should be conducted for more clarity on the subject, besides a timely medical intervention and treatment could possibly avoid the rising morbidity associated with the disease.